Human umbilical cord mesenchymal stem cells attenuate podocyte injury under high glucose via TLR2 and TLR4 signaling. (March 2021) - Wang, Yinghui; Liu, Jiaxi; Zhang, Qingqing; Wang, Weiwei; Liu, Qingzhen; Liu, Shanshan; Song, Yan; Wang, Xueling; Zhang, Yaping; Li, Shan; Yang, Xue; Lv, Shasha; et al.
Abstract: Aims: This research aimed to investigate the effects of high glucose (HG) on the innate immunity of podocytes and diabetic nephropathy (DN) mice via Toll like receptor (TLR) signaling, and explore the protective effects of human umbilical cord mesenchymal stem cells (HUC-MSCs) on this process. Methods: HUC-MSCs obtained from human umbilical cord were cocultured with podocytes and transplanted into DN mice. Flow cytometry, CCK-8assay, ELISA, western blot analysis, periodicacid-schiff, masson, immunohistochemistry and immunofluorescence staining was used to detect the inflammation, TLR signaling, physical, biochemical and morphological parameters in podocytes and DN mice. Results: HG reduced the viability of podocytes, activated TLR2 and TLR4 signaling pathway and increased the expression of inflammatory cytokines such as IL-6, IL-1β, TNF-α, and MCP-1 in podocytes and DN mice. However, HUC-MSCs decreased the inflammation and restrained the TLR signaling pathway caused by HG in vitro and in vivo. Furthermore the rhHGF decreased the expression of TLR2 and TLR4 while the blockade of HGF increased the expression of TLR2 and TLR4 in podocytes. Conclusions: HUC-MSCs have benefits to the podocytes under HG and the progression of DN by inhibiting TLR signaling pathway and depressing the inflammation. HUC-MSCs may be a therapeutic strategy for treating patients with DN.